Ice-Water Phase Change Studies in Plastic and Non-Plastic Silts - Bheemasetti, Tejo V.; Tohm, Calvin; Lingwall, Bret N. (Frontiers in Built Environment, 2022)
This paper presents experimental results and analysis of change in freezing characteristics of clays and silts with change in pH and moisture content in the pore structures. The plastic and non-plastic silts and clays in the cold regions undergo significant changes in thermal properties causing non-equilibrium thermal conditions which can lead to frost-heave, thaw-weakening, and thawing-induced landslides, and mass wasting events. In geotechnical engineering, particularly in cold regions, a soil's thermal properties play a large role in the design, functionality, and longevity of an earthen structure. The thermal properties of the soil will also govern the porous media phase changes influencing thermal hysteresis, and heat capacity in soils. These variables will change with seasonal freeze-thaw cycles which can lead to changes in a soil's structure, fabric, density, moisture content, and strength over time. With global warming causing the temperatures to gradually rise over time, the rapidly varying seasonal freeze-thaw cycles are now becoming an issue in areas where the designs have relied heavily on the permafrost. This research study investigates the fundamental changes to freezing and thawing characteristics of plastic and non-plastic silts with changes in frost penetration rates (cooling rate); moisture content (liquid limit, plastic limit, and optimum moisture content); pH (2 to 7); and soil type with different percentages of fines content and specific surface area.